Moronidae Jordan & Evermann 1896 ... - Golani, Daniel; Fricke, Ronald (Zenodo, 2018)
MORONIDAE Dicentrarchus labrax (Linnaeus 1758) Gulf of Suez: Egypt (Steindachner 1895, as Labrax lupus; Gruvel 1936, as Morone labrax). Gulf of Aqaba: Israel (Golani & Lerner 2007), Jordan (Khalaf & Disi 1997). Red Sea main basin: ¯ General distribution: Western Baltic Sea, North Sea, Mediterranean Sea, Black Sea, eastern Atlantic: Norway and Iceland to Senegal. Remark: Originally in the eastern Atlantic and Mediterranean; introduced in the Red Sea. Dicentrarchus punctatus (Bloch 1792) Gulf of Suez: Egypt (Steindachner 1895, as Labrax orientalis; Ben-Tuvia 1971). Gulf of Aqaba: Egypt (Ben-Tuvia, 1971). Red Sea main basin: ¯ General distribution: Mediterranean Sea, eastern Atlantic: English Channel to Senegal. Remark: Anti-Lessepsian migrant from eastern Mediterranean into Red Sea (see Ben-Tuvia 1971). ... : Published as part of Golani, Daniel & Fricke, Ronald, 2018, Checklist of the Red Sea Fishes with delineation of the Gulf of Suez, Gulf of Aqaba, endemism and Lessepsian migrants, pp. 1-215 in Zootaxa 4509 (1) on page 67, DOI: 10.11646/zootaxa.4509.1.1, http://zenodo.org/record/2607566 ...